Extended evaluation of the Volterra-Neural Network for model compression - Rubiolo, Mariano (2012)
When large models are used for a classification task, model compression is necessary because there are transmission, space, time or computing constraints that have to be fulfilled. Multilayer Perceptron (MLP) models are traditionally used as a classifier, but depending on the problem, they may need a large number of parameters (neuron functions, weights and bias) to obtain an acceptable performance. This work extends the evaluation of a technique to compress an array of MLPs, through the outputs of a Volterra-Neural Network (Volterra-NN), maintaining its classification performance. The obtained results show that these outputs can be used to build an array of (Volterra-NN) that needs significantly less parameters than the original array of MLPs, furthermore having the same high accuracy in most of the cases. The Volterra-NN compression capabilities have been tested by solving several kind of classification problems. Experimental results are presented on three well-known databases: Letter Recognition, Pen-Based Recognition of Handwritten Digits, and Face recognition databases.